(4x+7)-(6x-7)=

Simple and best practice solution for (4x+7)-(6x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+7)-(6x-7)= equation:


Simplifying
(4x + 7) + -1(6x + -7) = 0

Reorder the terms:
(7 + 4x) + -1(6x + -7) = 0

Remove parenthesis around (7 + 4x)
7 + 4x + -1(6x + -7) = 0

Reorder the terms:
7 + 4x + -1(-7 + 6x) = 0
7 + 4x + (-7 * -1 + 6x * -1) = 0
7 + 4x + (7 + -6x) = 0

Reorder the terms:
7 + 7 + 4x + -6x = 0

Combine like terms: 7 + 7 = 14
14 + 4x + -6x = 0

Combine like terms: 4x + -6x = -2x
14 + -2x = 0

Solving
14 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -2x = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -2x = 0 + -14
-2x = 0 + -14

Combine like terms: 0 + -14 = -14
-2x = -14

Divide each side by '-2'.
x = 7

Simplifying
x = 7

See similar equations:

| 3m-k=k | | 2n+yr=r-9f | | 21/2=x/16 | | 20c-30=370 | | x^2+34-152=0 | | 5(5t-10)=67 | | 20+n=84 | | 2/5x0.063= | | (a^3/6)^-3 | | x/9-2=2 | | 3/8=12/ax | | 13j-13=13 | | (10x+4)-(5x-2)=12 | | 15-8v=-11v-45 | | 3x+12+x=4(3+x) | | (10x-4)-(5x-2)=12 | | -8a-5+4a=-125 | | -6x-8=?/;. | | 7/12•4/21 | | -8a-5+4a=125 | | 5x+2-5x-2=12 | | 2.5(12.75x+24.50)= | | 7d/2.5=14.88 | | -8a-5-4a=125 | | 7x+4-6x=-5 | | 31-10x=10+11x | | (4x/5y)^3z | | 4x^4+40w^2-44=0 | | 8(6-6t)= | | 4x^4+40x^2+44=0 | | 30(p+5)=50 | | 8r^2+15r-2= |

Equations solver categories